Tinjauan Atas Asas-Asas Pemerintahan Daerah Dan Implementasi SOTK - Damar Tangguh Rabani; Diny Widya Evriyanti Simarangkir; Ericko Arwinda Al Iyad; Muhammad Rifki Adnan Ramadhan (Jurnal Relasi Publik, 2023)
There have always been ups and downs in regional governance, with a number of autonomy issues and less-than-perfect institutional working relationships between the Centre and the regions. Instead of being resolved by the 2014 Local Government Law, Law No. 23/2014, these issues have further complicated the relationship between local authorities and the central government. This research aims to analyze the review of the principles of regional government and the implementation of the SOTK. This research uses a normative juridical method that focuses on legal precedents, relevant laws, and regulations. The result of this research is that regional autonomy is based on the idea that autonomous regions have the authority as well as the rights and obligations in managing their own local interests in accordance with the law. In Indonesia, local governance is guided by three basic principles, namely 1) The principle of decentralization. 2) The idea behind de-concentration. 3) Assistance tasks as a concept. There are three parts to the model of how local governments and the federal government work together, namely 1) agency model, 2) the interaction Model, and 3) the relative Autonomy Model The structure of each region will include various interventions. However, the drafting guidelines from the government make the SOTK look uniform, centralized and rigid, so despite the differences, each region's SOTK still has some similarities.